Clinical outcomes of DNA-damaging agents and DNA damage response inhibitors combinations in cancer: a data-driven review - Fontenot, Rick; Biyani, Neha; Bhatia, Kishor; Ewesuedo, Reggie; Chamberlain, Marc; Sharma, Panna (Frontiers in Oncology, 2025)
The combination of DNA-damaging agents (DDAs) and DNA damage response inhibitors (DDRis) has been extensively studied to improve therapeutic outcomes. While both groups of agents show promise individually, DDAs are limited by tumor resistance, and DDRis are limited by specific genetic context. Combining DDAs with DDRis may overcome these challenges and enhance patient outcomes. This review systematically analyzes clinical trials investigating the combination of DDAs and DDRis by dividing them into two sections: PARP and non-PARP inhibitors. An evaluation was conducted on 221 DDA-DDRi combination-arm trials involving 22 DDAs and 46 DDRis. DDAs were classified into eight subclasses, and DDRis into 14 distinct subclasses based on their mechanisms of action and specific targets, respectively. 89 of the 221 combination-arm trials had interpretable outcomes and were selected for further analysis. These were assigned outcome scores based on predefined criteria, reflecting their clinical effectiveness, safety, and benefit across different tumor types and patient populations. Our analysis emphasizes the patterns in treatment effectiveness, safety, and emerging trends across various cancer types and discusses the potential of biomarkers to guide treatment selection and improve patient outcomes. This review outlines an understanding of the recent state of DDA-DDRi combinations, offering critical insights for refining future cancer treatment strategies.